2011
DOI: 10.1098/rsif.2011.0086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of skin hydration on the dynamics of fingertip gripping contact

Abstract: The dynamics of fingertip contact manifest themselves in the complex skin movements observed during the transition from a stuck state to a fully developed slip. While investigating this transition, we found that it depended on skin hydration. To quantify this dependency, we asked subjects to slide their index fingertip on a glass surface while keeping the normal component of the interaction force constant with the help of visual feedback. Skin deformation inside the contact region was imaged with an optical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
124
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 46 publications
14
124
0
Order By: Relevance
“…Figure 10a shows the best fits to the low normal force data reported by André et al [95], which demonstrates that equation (4.3) provides a first-order description of the trends for these datasets. The best-fit values of m for the data corresponding to W ¼ 0.6 N are given in table 2.…”
Section: Evolution Of Slip In the Contact Regionmentioning
confidence: 90%
See 3 more Smart Citations
“…Figure 10a shows the best fits to the low normal force data reported by André et al [95], which demonstrates that equation (4.3) provides a first-order description of the trends for these datasets. The best-fit values of m for the data corresponding to W ¼ 0.6 N are given in table 2.…”
Section: Evolution Of Slip In the Contact Regionmentioning
confidence: 90%
“…Initially at small applied tangential loads, André et al [95] observed in some cases that there was a small reduction in the gross area of contact before a slip annulus was initiated. Presumably this involves a peeling mechanism.…”
Section: Evolution Of Slip In the Contact Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of the apparent area of contact arising from the deformation of a finger pad has been examined using optical imaging during incipient slip (11); at different force levels (12,13); at different moisture contents (14) and tangential loads leading to slip (15); under rotation and lateral sliding movements over flat, raised, or indented glass surfaces (10); during stickto-slip transitions in distal, proximal, radial, and ulnar directions (16); over complete stick-to-slip epochs (17); and under the effects of oscillating loads (18,19).…”
mentioning
confidence: 99%